Högstubbar i gallring – kostnadseffektiv naturvård? - Eriksson, Andreas (2015)
A great difference between managed forest and natural forest is the amount of dead wood. To maintain biodiversity the practice of artificial creation of high-stumps has been established as a common measure in thinning operations. In this study I try to show the benefits of this measure, calculate the cost and study the opinions about it. Studying previous research I show that many endangered species are dependent of dead wood and that they have specific requirements of the quality. Artificial creations of high-stumps in thinning operations can´t see to all these requirements but contribute by continuous provision and spatial distribution. The cost is calculated as the net loss value for a single tree. The cost is very low and the measure of artificially create high-stumps which makes it cost-efficient, especially in comparison with other measures like set-asides. The study of opinions shows a positive attitude but the contractors pointed out the net loss and the risk of forest damage from insects as drawbacks. More information is demanded. Based on this study I call for artificial creation of high-stumps in all thinning operations, that the high-stumps should vary in many ways and that the norm of creating three per ha should be raised considerably.